Core Practices for Preservice Teachers in Physical Education Teacher Education. Issue 5 (12th June 2020) - Ward, Phillip; Higginson, Kelsey; Cho, Kyuil
Abstract : This article contributes to the ongoing discussion on practice-based teacher education in physical education teacher education (PETE) programs. In this article we situate core practices within the practice-based teacher education movement, define and describe core practices for physical education, and discuss how to use them in the PETE curriculum and in coursework. Defining the knowledge base of PETE, in this case in terms of core teaching practices, has several advantages. First, it creates a consensus on what is the knowledge base, which in turn can be refined or challenged. Second, it allows for a shared professional language to be used. Finally, it allows curriculum maps to be used to structure the intentional and detailed development of core practices across a PETE program.